PENDISTRIBUSIAN SAMPAH DI KABUPATEN SIDOARJO MENGGUNAKAN APLIKASI SIMULASI - Tamyiz, Muchammad; Prasetyo, Waluyo (Journal of Research and Technology, 2018)
The population of Sidoarjo Regency with a relatively high number and growth rate has consequences for the increase of waste produced volume. Increasing of volume waste is directly proportional to the increase in population, meaning that amount of waste produced is increasing (organic and inorganic waste). The TPA center in one of the garbage collection locations in Sidoarjo Regency has exceeded capacity (overload). This research was conducted with the aim of describing initial model of the distribution of waste used, evaluating initial performance model of waste distribution in Sidoarjo Regency, and providing recommendations to propose improvements in the waste distribution model used. The method applied in this study was using simulation. Based on the simulation results, the Third Scenario proposed the route with the most efficient distance, this affected the vehicle's operational time and the operational costs needed.